2009
DOI: 10.1021/ja809464e
|View full text |Cite
|
Sign up to set email alerts
|

Mononuclear Copper(II)−Superoxo Complexes that Mimic the Structure and Reactivity of the Active Centers of PHM and DβM

Abstract: Mononuclear copper(II)-superoxo complexes 2(X)-OO(*) having triplet (S = 1) ground states were obtained via reaction of O(2) with the copper(I) starting materials 1(X) supported by tridentate ligands L(X) [1-(2-p-X-phenethyl)-5-(2-pyridin-2-ylethyl)-1,5-diazacyclooctane; X = CH(3), H, NO(2)] in various solvents. The superoxo complexes 2(X)-OO(*) mimic the structure [tetrahedral geometry with an end-on (eta(1))-bound O(2)(*-)] and the aliphatic C-H bond activation chemistry of peptidylglycine alpha-hydroxylatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
182
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(198 citation statements)
references
References 28 publications
16
182
0
Order By: Relevance
“…Cu-superoxide species have been proposed as reactive intermediates in H-atom abstraction in the noncoupled binuclear Cu enzymes (1,29,30), although a Cu(II)-superoxide enzyme species has yet to be spectroscopically characterized. Alternatively, a variety of inorganic Cu(II)-superoxide model complexes have been trapped at low temperature (31)(32)(33)(34)(35). These include a diazacyclooctane supported complex (1) (32) (SI Appendix, Fig.…”
Section: Results and Analysismentioning
confidence: 99%
“…Cu-superoxide species have been proposed as reactive intermediates in H-atom abstraction in the noncoupled binuclear Cu enzymes (1,29,30), although a Cu(II)-superoxide enzyme species has yet to be spectroscopically characterized. Alternatively, a variety of inorganic Cu(II)-superoxide model complexes have been trapped at low temperature (31)(32)(33)(34)(35). These include a diazacyclooctane supported complex (1) (32) (SI Appendix, Fig.…”
Section: Results and Analysismentioning
confidence: 99%
“…In support of this capability, complex 82 (R ¼ phenethyl group) decays to yield 86 ( Figure 40) via a pathway shown by kinetic experiments and DFT calculations to proceed by ratelimiting intramolecular hydrogen atom abstraction by the coordinated superoxide from the benzylic C-H bond of the ligand phenethyl arm [286,287].…”
Section: Mononuclear Models Of Monocopper Active Sites In Enzymesmentioning
confidence: 90%
“…While not yet characterized by X-ray crystallography, adducts 81-85 have been studied by spectroscopy and theory, which also support end-on Cu(II)-superoxo formulations [285][286][287][288][289][290][291]. Like 80, all are best described as having triplet ground states, with an initial report of 81 being a singlet [285] having been subsequently refuted through VTVH-MCD and NMR spectroscopy [291].…”
Section: Mononuclear Models Of Monocopper Active Sites In Enzymesmentioning
confidence: 96%
“…Along this line, lots of copper(II) complexes with different ligands have been widely studied [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], because copper, as a biologically relevant element, shows great effects on the endogenous oxidative DNA damage associated with aging and cancer and relates to many enzymatic activities which have been identified. Comparing the number of studies dealing with monocopper complexes [14][15][16][17][18][19][20][21][22], relatively few studies on dicopper(II) complexes have been reported to date. However, the enhancement of DNA-binding activity for dinuclear complexes prompts us to design and synthesize new dicopper(II) complexes in order to gain some insight into their DNA/protein binding property and antitumor activity of these kinds of complexes [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%